Evaluation of various culture and staining techniques for the detection of extra pulmonary tuberculosis - Gupta, Seema; Goyal, Rahul K.; Bareja, Rajesh; Behara, Rabindra N. (International Journal of Research in Medical Sciences, 2016)
Background: Though pulmonary tuberculosis form is the commonest presentation, the extra pulmonary tuberculosis (EPTB) is also an important emerging clinical problem. The objective of the current study was to compare two staining techniques, Ziehl-Neelsen (ZN) stain, fluorescent stain and two-culture medium, solid Löwenstein-Jensen (LJ) medium and liquid 7H9 Middle brook medium in MGIT (Mycobacterium Growth Indicator Tube) 320 system, for detection of Mycobacterium in clinically suspected patients of EPTB. Methods: A total of 100 clinically suspected cases of EPTB samples from various extrapulmonary sites had been collected. All the specimens were stained with ZN stain and fluorescent stain. The culture were processed after decontamination of specimens with NaOH-NALC method and thereafter inoculated on solid and liquid culture medium. Results: Out of the 100 EPTB specimens, 30 were found positive by any of the above techniques used. Out of 30 positive cases 18 showed positivity by ZN staining while 20 showed positivity by fluorescent staining technique. In two culture methods, 27 isolates were grown by any of the culture system. Out of 27, 22 and 26 specimens showed growth of MTB complex on LJ media and MGIT culture system respectively. In AFB smear positive specimens, the average turnaround time was found to be 8.45 days and 22.5 days in MGIT and LJ medium culture assay respectively. While the turnaround times in AFB smear negative cases, it was 16.5 days and 32.3 days in MGIT and LJ medium culture assay respectively. Conclusions: MGIT was a dependable, highly efficient system for recovery of MTB complex for EPTB specimens in combination with LJ media.